Academic Staff Attitudes Towards the Use and Production of Networked Learning Resources - Plewes, Louise; Issroff, Kim (Proceedings of the International Conference on Networked Learning, 2002)
This paper describes part of a project to explore the use and production of learning resources. The project uses data from a series of in-depth interviews with staff at a large, multi-faculty research-oriented institution. Here we discuss briefly general findings from the interviews, but focus specifically on case studies of two academics, their use of and attitudes towards networked learning resources. Both have experience with a variety of types of learning resources, but have contrasting attitudes towards networked learning resources. Academic 1 (A1) is generally positive and Academic 2 (A2) has mixed views. We analyse the reasons for these complex attitudes and conclude that the local context of experience, plus other social and cultural factors are as important an influence as general factors such as staff training and technology.